Distributed robust fault-tolerant consensus control for a class of nonlinear multi-agent systems with intermittent communications - Sader, Malika (2022)
This paper considers the H∞ consensus problem for a class of nonlinear multi-agent systems in the presence of multiple faults, including intermittent communications and actuator faults, under the switching communication topologies. Aiming at this problem, a new distributed robust fault-tolerant controller is designed by utilizing an adaptive mechanism to remove the interference of nonlinear functions and multiple faults. Furthermore, the closed-loop system is proven to be stable by applying the topology-based average dwell time technique and the Lyapunov stability theory. Compared with existing controllers for nonlinear multi-agent systems, the developed scheme is efficient for solving the fault-tolerant H∞ consensus problem of nonlinear multi-agent systems even under the influence of intermittent communications, actuator faults, and switching communication topologies. Finally, an example based on the B747-100/200 aircraft model is given to validate the proposed control scheme's effectiveness.